(untitled) (University Journal of Zoology, Rajshahi University, 2008)
This study dealt with physical, chemical and microbiological characteristics of the lipid obtained from Mystus vittatus and some nutritional properties of the fish. The fish was found to contain moisture 76.98%, calcium 521.072 mg / 100gm, vitamin C 11.276 mg / 100 gm., lipid 1.89%, and protein 10.94% respectively. The specific gravity, refractive index and co-efficient of viscosity of this lipid were recorded as 0.935 at 30°c, 1.4662 at 30°c and 409.26 millipoise at 30°C respectively. The saponification value, iodine value, peroxide value, acid value, percentage of free fatty acid, percentage of unsaponifiable matter , Reicher-Meissel value, Polenske value and Acetyl value were found to be 218.12, 96.17, 1.79, 1.92, 0.968, 0.632, 0.932, 0.652 and 11.97 respectively. The GLC analysis revealed that the lipid is composed of palmitic acid (30.79%), oleic acid (29.50%), palmotelic acid (15.97%), stearic acid (11.89%), linoliec acid (5.43%), myristic acid (5.15%), lauric acid (1.07%), arachidic acid (.57%). The chloroform extract of this lipid showed some microbiological actively. The minimum inhibitory concentration of the extract was 0.5 μl/ ml against Staphylococcus aureus (107 cells/ ml) and 0.125μl/ ml against Shigella dysenteriae (107 cells/ ml). Key words: Physico-chemical, fish nutrition, M. vittatus Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 21-25